UMUR SIMPAN KOPI LENGKUAS INSTAN MENGGUNAKAN METODE ACCELERATED SHELF LIFE TESTING (ASLT) DENGAN PENDEKATAN PERSAMAAN ARRHENIUS - Ratih Yuniastri; Ismawati Ismawati; Dyah Ayu Fajarianingtyas (Universitas Tribhuwana Tunggadewi, 2019)
Galangal is one of the herbaceous plants that thrive in the Sumenep area and has been utilized by one of the Agro-industries in this area to become an instant galangal coffee product. Galangal processed products are one way to extend the shelf life of galangal. A decrease in quality during product storage can have an impact on the shelf of the product. To provide food safety guarantees for consumers and to support the creation of food independence, information about the shelf life of this product needs to be included. This research is to estimate the shelf life of instant galangal coffee products using the Accelerated Shelf Life Testing (ASLT) method with the Arrhenius approach, using a randomized block design (RBD). An increase in color and water content of instant galangal coffee indicates a decrease in product quality during the storage process. The parameter used to estimate the shelf life of products based on research results is water content. The initial water content of 5,237% with a critical water content of 18,67% and based on the Arrhenius equation the rate of water content increase was K = 656,94.e-3150,7(1/T). The shelf life of the instant galangal coffe product under study was 671 days at storage temperature 30oC; 411 days at 45oC: and 352 days at 50oC wit RH condition maintained at 70%.